Discovery of two new classes of potent monoamine oxidase-B inhibitors by tricky chemistry. Issue 14 (12th January 2015) - Cagide, F.; Silva, T.; Reis, J.; Gaspar, A.; Borges, F.; Gomes, L. R.; Low, J. N.
Abstract : Discovery of monoamine oxidase-B inhibitors based on chromane-2, 4-dione and chromone-3-carboxamide scaffolds for the management of neurodegenerative diseases. Abstract : The discovery of potent and selective monoamine oxidase-B inhibitors for the management of neurodegenerative diseases such as Alzheimer's and Parkinson's diseases is still a challenging endeavor. Herein, we report the discovery of two new classes of potent and selective MAO-B inhibitors based on chromane-2, 4-dione and chromone-3-carboxamide scaffolds.